Escape from Preferential Retention Following Repeated Whole Genome Duplications in Plants - Schnable, James C.; Wang, Xiaowu; Pires, J. C.; Freeling, Michael (Frontiers in Plant Science, 2012)
The well supported gene dosage hypothesis predicts that genes encoding proteins engaged in dose-sensitive interactions cannot be reduced back to single copies once all interacting partners are simultaneously duplicated in a whole genome duplication. The genomes of extant flowering plants are the result of many sequential rounds of whole genome duplication, yet the fraction of genomes devoted to encoding complex molecular machines does not increase as fast as expected through multiple rounds of whole genome duplications. Using parallel interspecies genomic comparisons in the grasses and crucifers, we demonstrate that genes retained as duplicates following a whole genome duplication have only a 50% chance of being retained as duplicates in a second whole genome duplication. Genes which fractionated to a single copy following a second whole genome duplication tend to be the member of a gene pair with less complex promoters, lower levels of expression, and to be under lower levels of purifying selection. We suggest the copy with lower levels of expression and less purifying selection contributes less to effective gene-product dosage and therefore is under less dosage constraint in future whole genome duplications, providing an explanation for why flowering plant genomes are not overrun with subunits of large dose-sensitive protein complexes.